Averee - Phillips, Stephanie, 1991-; Johnson, Dave, 1966- (A Wave Blue World, 2021)
In a world where one's social media rank determines their success in life, an average teenager named Averee suffers when her rank suddenly drops overnight, resulting in her getting banished from restaurants and her mother losing her job. Averee teams up with her best friend Zoe, a bottom-ranked rebel and her crush Luke to infiltrate the Ranked app's headquarters to sabotage its control over people's lives.